Evolution of Quality Assurance for Clinical Immunohistochemistry in the Era of Precision Medicine. Part 3: Technical Validation of Immunohistochemistry (IHC) Assays in Clinical IHC Laboratories. Issue 3 (March 2017) - Torlakovic, Emina E.; Cheung, Carol C.; D'Arrigo, Corrado; Dietel, Manfred; Francis, Glenn D.; Gilks, C. Blake; Hall, Jacqueline A.; Hornick, Jason L.; Ibrahim, Merdol; Marchetti, Antonio; Miller, Keith; van Krieken, J. Han; et al.
Abstract : Validation of immunohistochemistry (IHC) assays is a subject that is of great importance to clinical practice as well as basic research and clinical trials. When applied to clinical practice and focused on patient safety, validation of IHC assays creates objective evidence that IHC assays used for patient care are "fit-for-purpose." Validation of IHC assays needs to be properly informed by and modeled to assess the purpose of the IHC assay, which will further determine what sphere of validation is required, as well as the scope, type, and tier of technical validation. These concepts will be defined in this review, part 3 of the 4-part series "Evolution of Quality Assurance for Clinical Immunohistochemistry in the Era of Precision Medicine."